Inclusive Classroom Practices and Challenges from the Lens of the Teachers in a Rural School - Retiza, Dyesebel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the inclusive classroom practices employed by teachers, the challenges they encountered, and the measures proposed to strengthen inclusive education at San Vicente Elementary School, a rural public elementary school in Uson South District, Division of Masbate. The study was anchored in a conceptual framework linking teachers’ inclusive practices, implementation challenges, and recommendations for improvement. It employed a qualitative phenomenological design involving all seven Kindergarten to Grade 6 teachers selected through complete enumeration sampling. Data were gathered using a validated semi-structured interview guide and analyzed through thematic analysis. The findings showed that teachers implemented differentiated and learner-centered instruction, individualized support, flexible grouping, peer tutoring, cooperative learning, varied instructional materials, positive behavior management, and supportive classroom routines to address diverse learner needs. However, they encountered difficulties in managing learners with varying academic, behavioral, emotional, and social needs, particularly in large classes. Other challenges included insufficient instructional materials and assistive technologies, inadequate facilities, limited access to specialized personnel and support services, and insufficient professional training in inclusive education. Despite these constraints, teachers demonstrated patience, adaptability, resourcefulness, and commitment to promoting learner participation and inclusion. The study concluded that effective inclusive education in rural schools requires sustained teacher development, adequate learning resources, specialized assistance, improved facilities, and coordinated support from school administrators, families, communities, and educational authorities. It recommends continuous professional development, stronger institutional and stakeholder collaboration, improved resource allocation, and expanded learner-support mechanisms. The study supports SDG 4 on Quality Education, SDG 5 on Gender Equality, and SDG 10 on Reduced Inequalities by promoting equitable participation and access to learning. It contributes to educational, institutional, community, and policy sustainability by providing localized evidence for strengthening inclusive education in resource-constrained rural schools.
Keywords: Classroom Management; Differentiated Instruction; Inclusive Classroom Practices; Inclusive Education; Rural School; Teacher Experiences; Teacher Preparedness